(untitled) (Archives of Clinical Psychiatry, 2008)
BACKGROUND: The combination of drugs for the treatment of psychiatric disorders has become a relatively frequent practice. The antidepressants are involved in several clinically important pharmacological interactions. OBJECTIVES: To detect the risk of interactions between antidepressants and associated drugs prescribed for adults patients. METHODS: Data on 151 medical prescriptions of antidepressants and other psychiatric drugs were retrospectively assessed at a teaching pharmacy in the city of Cascavel (state of Parana, Brazil), between October and November 2005. Only prescriptions provided for adults patients (19 years and older) were analyzed. RESULTS: Prescriptions were most frequently provided for female patients (64.9%), and for patients in the 31 to 40 year-old age group (32.5%). Considering prescription information only, we identified a clinically relevant risk of drug-drug interactions in eight prescriptions of tricyclic antidepressants (TADs) and associated drugs; the putative consequence of such pharmacological interaction was considered moderately relevant in four of these. The co-prescription of selective serotonin reuptake inhibitors (SSRIs) with other related drugs bearing a putative risk of interaction was observed in 16 cases, two of which involved a significant risk, ten a moderate risk, and four a minor risk of clinically relevant consequences. DISCUSSION: We provide evidence that the risk of pharmacological interactions may be often overlooked in the prescription of antidepressants (TAD and SSRIs) and related drugs in this clinical setting.